5, 10, 15, 20-tetrakis-(4-methoxyphenyl) porphyrin film/K+ ion-exchanged optical waveguide gas sensor. (August 2020) - Mamtmin, Gulgina; Kari, Nuerguli; Abdurahman, Renagul; Nizamidin, Patima; Yimit, Abliz
Highlights: 5, 10, 15, 20-tetrakis-(4-methoxyphenyl) porphyrin deposited OWG sensor is reported. Change the acidity of the porphyrin solution used to prepare sensitive layer. The acidity of the porphyrin solution affects the sensing devices performances. Sensors have the potential to be used in food testing and environmental monitoring. Abstract: Optical waveguide (OWG) sensors are widely used in gas detection, and sensitive materials are the key factors affecting sensor performance. Herein, we report on a 5, 10, 15, 20-tetrakis-(4-methoxyphenyl) porphyrin (TMP) deposited optical wave guide (OWG) sensor. The porphyrin solutions with different acidity were deposited on a K + -ion exchanged glass OWG surface by spin coating, to fabricate porphyrin film-coated OWG gas sensing devices. The effects of pH values of the porphyrin solution used to prepare the sensitive film on the sensing properties of these devices were investigated. The gas sensitive performances of these devices in response to analytes were compared. Among them, the sensing devices fabricated using original and acidic solutions of porphyrin exhibited significant responses to sulfide gases and ethanediamine, respectively. The sensing device prepared using an acidic solution has a good response to ethanediamine gas (response and recovery times of the sensor for 1 ppm of EDA (ΔI = 48) are 13 and 38 s, respectively). The RSD of the output light intensity is ±2.84, the signal to noise ratio (S/N) is 5.6. The device prepared using the original solution has an excellent response to sulfide gases (H2 S, SO2 ), and can detect low concentration levels (ppm) of sulfide gases. These sensing devices thus have the potential to be used in food quality testing and environmental monitoring.